The cognitive underpinnings of policy process studies: Introduction to a special issue of Cognitive Systems Research. (October 2017) - Jones, Bryan D.; Thomas, Herschel F.
Abstract: This article introduces the special issue of Cognitive Systems Research on public policy processes. We begin with a discussion of the cognitive foundations of public policy that stem from the complexity of human cognition and emotion. Next, we provide an overview of the articles in the special issue, which occur at the edge of a public policy-cognitive systems boundary. We then turn to a discussion of promising new work in the study of public policy that explores—or may benefit from—the cognitive systems perspective.